NARRATIVE REVIEW AND ERIKSONIAN-SYNTHESIS OF LESSONS FROM ANIMALS: MUTUALITY OF RECOGNITION IN THE AGE OF THE PSEUDO SPECIES. - Nicola Wannenburg; Gasson, James; van Niekerk, Roelf (Student’s Journal of Health Research Africa, 2024)
Violence in society has become more pervasive in all facets of life and is often rationalized by the formation of ‘unique identities’. Homes, communities, and places of education have all been implicated. On-going violence and destruction also lead to issues surrounding the sustainability of the environment and the potential long-term impact on humans and animals. Despite technological advancement making the world a smaller place, it has not necessarily brought people together. Increased alienation from the self as well as other people and nature has been associated with decreased stability and increased psychological distress. Post the Covid-19 pandemic there has been a call for greater focus on One Health, which views the health of humans, animals, and nature as interlinked. Animals as aids for healing is ever increasing in medical and therapeutic settings. Increased focus on retaining the healing aspects of nature and relationships with animals in an ever-changing society and technological world may assist a move to a holistic approach to living, education, and ethical treatment of others and the environment. Further research is needed on children’s and adults’ understanding of affective empathy and ethical action. Research as well as guidance on the ethical treatment of others may inform school curriculums and may encourage an ethical stance to policy development as well as implementation. An Eriksonian synthesis on lessons from animals regarding mutuality of recognition in an ecologically bound universe is offered as one lesson and philosophy that may facilitate ethical thinking and action.